Optimizing students’ self-discipline through self-management techniques in group counselling - Paksa, Kadek Aprilia; Metra Putri, Dewi Arum Widhiyanti; Gading, I Ketut; Suarni, Ni Ketut (Universitas Islam Negeri Raden Intan Lampung, 2026)
Self-discipline problems among senior high school students have been a recurring issue, particularly among twelfth-grade students who often arrive late, delay their school assignments, and violate school regulations. This study was conducted at SMA Negeri 5 Denpasar with the purpose of determining whether group counseling using self-management techniques could help improve students’ self-discipline. The research design used in this study was a pre-experimental, one-group pre-test–post-test design, since the school setting did not allow a control group to be formed. Forty-five students were screened first using a self-discipline scale consisting of 30 items in a five-point Likert format (CVI = 0.89; item-total correlation = 0.42–0.76; Cronbach’s α = 0.87), and eight students with a low self-discipline category were selected through purposive sampling. The participants consisted of five female and three male students, aged between 17 and 18 years. The intervention was given in six group counseling sessions, 60 minutes per session, conducted twice a week over three weeks. Four techniques were applied during the sessions, namely self-monitoring, self-contracting, self-reinforcement, and stimulus control. The results of the analysis showed that the mean self-discipline score increased from 61.25 (SD = 2.05; 95% CI [59.67–62.83]) at pre-test to 75.75 (SD = 2.43; 95% CI [73.82–77.68]) at post-test, or by approximately 23.7%. The Wilcoxon Signed-Rank Test was used to test the difference between the pre-test and post-test scores, and the result was statistically significant (Z = −2.52; p = 0.012), with a large effect size (r = 0.89). Based on these results, the self-management intervention in group counseling may contribute to the improvement of students’ self-discipline, although the results should be interpreted with caution. The limitations of this study include the small number of participants, the absence of a control group, and the lack of a longer-term follow-up of the students. Therefore, further research is needed using a stronger experimental design, a larger and more representative sample, and a longer measurement period.